Audio description and inclusive teaching. A study on listening comprehension and ability of empathy. - Andrea Fiorucci (Firenze University Press, 2017)
The paper presents quantitative and qualitative research aims to evaluate the didactic functionality, listening comprehension in film narrative and promoting inclusion, of audio description: is a support service whose main goal is to reduce the visual deficit by making accessible any audiovisual content with appropriate substitute information. In primary classes, according to three different phases and modes of reception, it has been proposed audiovisual Kirikou and the Sorceress: animation feature film written and directed in 1998 by Michel Ocelot and audio described by the CNTHI, University of Salento in 2012 (Fiorucci, 2012; Pinnelli, 2012). Data analysis shows that the different modes of audiovisual enjoyment have allowed the classroom setting to live an unusual learning experience aimed at promoting, through the empathy and multisensoriality, inclusion at school.   Audio descrizione e didattica inclusiva. Una ricerca sulla comprensione da ascolto e la capacità di immedesimazione. Il contributo presenta una ricerca quali-quantitativa finalizzata a valutare la funzionalità didattica, comprensione da ascolto del linguaggio narrativo-filmico e promozione dell'inclusione, dell'audio descrizione: un servizio di supporto il cui obiettivo principale è ridurre il deficit visivo, rendendo accessibile qualsiasi contenuto audiovisivo con appropriate descrizioni sostitutive. In nove classi primarie, secondo tre diverse fasi e modalità di fruizione, è stato proposto l'audiovisivo Kirikù e la strega Karabà: lungometraggio per bambini scritto e diretto nel 1998 da Michel Ocelot e audio descritto dal gruppo di ricerca del CNTHI dell'Università del Salento nel 2012 (Fiorucci, 2012; Pinnelli, 2012). L'analisi dei dati conferma che le diverse modalità di fruizione dell'audiovisivo hanno permesso al contesto classe di vivere una insolita esperienza di apprendimento orientata a promuovere, attraverso l'immedesimazione e la multisensorialità, l'inclusione a scuola.